THE INFLUENCE OF STUDENT'S LEARNING INDEPENDENCE ON MATHEMATICS LEARNING OUTCOMES IN FLAT SHAPES - Rahmanita Nurul Aulia; Nedin Badruzzaman; Nurlinda Safitri (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
This study uses a quantitative method with a causal approach. while the respondents are fourth grade students of SD Negeri Leuwiliang 04 as many as 45 students. This research was conducted in the even semester of the 2021/2022 academic year. The results of the study show that there is an influence between the Independent Learning of Students (X) on Mathematics Learning Outcomes in the Flat Shape Material (Y) statistically proven by the results of the significance test and regression with the regression equation = - 9.60 + (0.99X). So it means that for every one unit increase in the learning independence variable, the learning outcomes of students will also increase by 0.99 units. The strength between the learning independence of students (X) on the learning outcomes of mathematics in the flat shape material (Y) is evidenced by the correlation coefficient of (rxy) 0.98 with a coefficient of determination of 96.04%. This has shown that the increase and decrease in mathematics learning outcomes is influenced by the level of learning independence of 96.04% while 3.96% comes from other factors. And the results of hypothesis testing H0 are rejected and Ha is accepted because tcount 5,436 ttable 1,645. Based on the results of data processing and discussion, it can be concluded that there is a fairly large positive influence between students' learning independence on mathematics learning outcomes in flat shape material. In other words, the greater the level of learning independence of students, the higher the learning outcomes of mathematics, and vice versa